Breivik – The Norwegian Terrorist Case. (22nd April 2014) - Syse, Aslak; Busch, Kenneth G.; Schouten, Ronald; Weissman, Sidney H.; Felthous, Alan R.
<x xml:space="preserve">Abstract</x> On July 22, 2011, there were two murderous attacks in Norway. Both assaults – the bombing of governmental buildings in Oslo City center and the lethal shooting down of young members of the Labour Party on an island – were planned and accomplished by a lone perpetrator. These episodes give rise to several interesting questions. What happened really, and how could it happen? Was the perpetrator sane or insane? What was the ideological background for the attacks? It is unnecessary to discuss in any detail whether or not these acts should be categorized as terrorism. However, there is good reason to consider what these terror attacks imply for Norwegian society at large. What significance did the attacks have for Norwegian democracy, and did they have any impact on the 2013 parliamentary elections? What will be the future for the offender, both in the short term and in years to come? What will happen to the Norwegian insanity defense? These questions are addressed in this article. Copyright © 2014 John Wiley & Sons, Ltd.